LEARNING SOCIETY SEBAGAt WAHANA MFMBANGUN KARAKTER BANGSA - HANUM, FARIDA (FOUNDASIA, 2005)
All members of a society have rights to receive education (education for all) and what exist in a society can be educational resources (all for education). If such a concept is applied with a full commitment, a learning society will result. A learning society can reflect an educated society, which can be attained through formal or non formal institutions. An educated society will produce morale and ethics, and a society with morale and ethics is one with a character and a self-esteem as a nation. It is what people in the world aspire.